The formation of CuInSe2 thin-film solar cell absorbers by laser annealing of electrodeposited precursors - Jost, Stefan Georg; Schurr, R.; Hergert, Frank; Hock, Rainer; Schulze, J.; Kirbs, A.; Voss, T.; Purwins, Michael; Palm, J.; Mys, I. (Solar Energy Materials and Solar Cells, 2008)
The formation of the compound semiconductor CuInSe2 by laser annealing of electroplated precursor films in inert gas atmosphere represents an entire non-vacuum production process of thin-film solar cell absorbers. Besides this technological aspect, the impact of extreme annealing rates on structural properties of the resulting semiconductor is interesting from a fundamental research point of view. For this reason, we compared absorbers processed by laser annealing with absorbers annealed with moderate heating rates in the range of 1 K/s by means of X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and energy-dispersive X-ray analysis (EDX). All absorbers processed with laser or furnace annealing consist of crystalline CuInSe2 in the chalcopyrite crystal structure with a high degree of cation disorder. We show that laser annealing does not lead to unintentional selenium loss during the semiconductor formation process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: CuInSe2; thin films; laser annealing; electrodeposition; non-vacuum processing